Exploring the potential of natural resources and cultural heritage in Karimun regency (Indonesia): the road to sports tourism development - Fadli Surahman; Setya Rahayu; Nasuka Nasuka; Sri Sumartiningsih; Heny Setyawati; Taufiq Hidayah; Hilda Oktri Yeni; Anas Ardiansyah; Muhamad Ichsan Sabillah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: The problem in this study is that there is still a lot of potential for sports tourism that has not been developed and utilized properly, this is because there is no effective activity program related to sports tourism.